COVID-19 Pneumonia in Patients with Chronic Myocarditis (HBV-Associated with InfarctLike Debute): Specifics of the Diseases Course, the Role of the Basic Therapy (Part II) - O. V. Blagova; N. V. Varionchik; M. M. Beraia; V. A. Zaidenov; E. A. Kogan; N. D. Sarkisova; A. V. Nedostup (Столичная издательская компания, 2020)
Chronic infectious-immune myocarditis of severe course can potentially be considered as a factor that aggravates the course of new coronavirus disease (COVID-19) and increases the risk of adverse outcomes. The interaction of chronic myocarditis and COVID-19 during long-term immunosuppressive therapy has not been studied. We present a description of a 35-year-old female patient with chronic infectious-immune myocarditis (morphologically confirmed, with a history of infarction-like onset and thromboembolic complications), who had continuous immunosuppressive therapy with methylprednisolone and mycophenolate mofetil. The patient also received new oral anticoagulants and tenofovir (for chronic HBV infection). COVID-19 (SARS-Cov-2 RNA+) was diagnosed in May 2020. Risk factors for the adverse course of coronavirus infection included severe obesity, heart failure, and life-threatening ventricular arrhythmias. Correction of immunosuppressive therapy (withdrawal of the cytostatic agent, administration of hydroxychloroquine) and therapy with levofloxacin, an interleukin-17 inhibitor (netakimab) were performed. The severity of pneumonia and respiratory failure was moderate despite high fever and high levels of inflammatory markers in the blood (including interleukin-6). Signs of exacerbation of myocarditis, increased levels of troponin T and anticardial antibodies (compared with the initial ones) were not found. It can be assumed that supportive immunosuppressive therapy for myocarditis has a positive effect on the course of coronavirus pneumonia and avoids exacerbation of myocarditis. Careful continuation of immunosuppressive therapy with temporary withdrawal of aggressive cytostatics can be recommended in chronic myocarditis. Further study of the features of the course of previous myocarditis and COVID-19 pneumonia is necessary.